Analysis of Illocutionary Acts And Perlocutionary Acts In The Freedom Writers By Richards Largavenese - Saeful Anwar (International Journal of English Learning and Applied Linguistics (IJELAL), 2022)
Pragmatics is a branch of linguistics that examines meaning in an externally meaningful way. A speech act is an utterance made by the following speakers’ notices, orders or regrets, congratulations, and words that always involve action or intent. This research is qualitative that identified the types of illocutionary acts and perlocutionary acts from The Freedom Writers. The data was then analyzed and categorized based on speech acts classification. The objective of this research is to know the type of Illocutionary act and Perlocutionary Act found in The Freedom Writers by Richards Lagravenese. The research findings of this study are; First, the writer found 139 kinds of illocutionary acts in The Freedom Writers, and out of them, there are 47 types of representative consists of stating, informing, suggesting, complaining, and claiming; 39 types of directive consists of ordering, commanding and requesting; 21 types of expressive consists of thanking, congratulating, blaming and praising; 19 types of commissive consists of promising and offering; and 13 types of declarative only consists of naming. Second, there are only 55 data on perlocutionary acts found in The Freedom Writers by Richards Lagravenese.